P437 Early therapeutic drug monitoring of Adalimumab, but not HLADQ*A1 determination, predicts inflammatory bowel disease outcome. (30th January 2023) - Carrillo Palau, M; Alonso-Abreu, I; Morant, A; Vera, B; Vela, M; Ramos, L; Franco, A; Reygosa, C; Barrios, Y; Medina Chico, J S; Globio, V; Hernández-Perez, A; et al.
Abstract: Background: Anti-TNF drugs are effective treatments for the management of Inflammatory Bowel Disease (IBD), yet treatment failure is common. Monitoring drug levels and their antibodies (ATIs) can be useful to optimize the management of patients. In addition, the HLA-DQA1*05 gene has been recently related as a possible marker of immunogenicity and loss of response to anti-TNF therapy.The aim of this study was to evaluate the clinical impact of determining adalimumab (ADA) levels and anti-adalimumab ATIs in patients with IBD, and the influence of the HLA-DQA1*05 allele on the response and maintenance of adalimumab treatment in this population. Methods: This observational, multicentric and prospective study enrolled patients who started treatment with ADA from October 2020 to October 2022. Demographic data and IBD characteristics were recorded. Clinical Activity Index (Harvey Index and Parcial Mayo Score) and C reactive protein(CRP), faecal calprotectin (FC), endoscopy or radiological activity, Global Physician Assesment (GPA) and PRO (by IBDQ-9) were prospectively collected at baseline and at the same time that ADA levels: week 4, 10, 30 and 12 months. HLA-DQA1*05 was genotyped at baseline. Pearson coefficient was used to assess the correlation between ADA levels and activity disease at different points Results: We included 131 (age 42±17 years, 56% female) IBD patients (78% Crohn`s Disease, 21% Ulcerative Colitis and 1% Indeterminate colitis) who started treatment with ADA (80% were naïve to anti-TNF and 57% started ADA combined with immunomodulator treatment). At baseline, 81% had an active disease (Global Physician Assesment=1), 49% had CRP >5 mg/L and 77% had FC > 150 mg/kg. PRO at baseline was 63±9.1. HLA was determined in 99 patients, of whom 42 (42%) were HLA-DQA1*05 positives. We found a positive correlation between PRO score and Hb levels and albumin, meanwhile a negative correlation with FC and CRP at week 0. No correlation with ADA levels or ATIs was established. Patients HLA-DQA1*05 positive had not more adverse reaction or ATIs during the observational period. Patients with ADA serum concentration >7µg/mL at week 4 had CRP <5mg/dL at week 4 (p=0.04) and at week 10 (p=0.01). Patients with ADA serum concentration >7µg/mL at week 10 had more stable disease (PGA =0) and CRP <5mg/L, FC <150 mg/kg at week 10 (p<0.05), CRP <5mg/L at week 30 (p<0.05) and FC <150 mg/kg at 12 months. Conclusion: Early Drug level monitoring of Adalimumab (after induction) may improve the management of IBD patients. Our study shows that ADA levels >7 µg/mL is associated with a better clinical response in short and long-term, independent of HLADQA1*05.